Quality Assurance in Managing Higher Education - Abiona, Olufemi Adebayo (International Journal of Educational Management, 2022)
Quality assurance in the management of higher education in Nigeria is a task that must be accomplished. Scholars in the education discipline continue to argue and ponder whether the quality of education in Nigeria is falling. In order to ascertain the past, present and future standard of education in any country, quality assurance mechanisms should be used to determine the state of the educational activities. Quality assurance refers to ways of ensuring that the quality of a service or product conforms with approved standards, during the processing or implementation stage. At the processing or implementation stage quality assurance ensures the use of high standard materials, appointment of qualified and competent staff, job allocation to the requisite and appropriate staff and timely completion of assignments. Abiona (2019). Furthermore, Lucey (2014) commented that quality assurance comprises administrative and procedural activities implemented in a quality system so that requirements and goals for a product, service or activity will be fulfilled.In educational affairs, quality assurance is the degree or ability to which tertiary institutions in Nigeria conform to the established standards. Quality assurance in education in Nigeria is also the adequacy of the teaching, learning and research activities to the needs of the recipients and that of the nation in general. Hence, adequacy of various input resources will certainly exercise tremendous influence on quality assurance in Nigeria education system. Education stakeholders including students should play their expected role and realize that it is part of their own responsibility to pursue the quality assurance agenda.